The degree of association between overweight and obesity with the use of electronic media among Bangladeshi adolescents. - Suvasish Das Shuvo; Biplob Kumar Biswas (PLoS ONE, 2023)
Background Electronic media usage is recently considered a modifiable risk factor for overweight and obesity among adolescents. The purpose of this present study was to evaluate the association of electronic media (EM) usage with overweight and obesity among school-going adolescents. Methods This cross-sectional study was conducted from October to December 2019 among school-going adolescents (14-16 years old) residing in the Jashore Sadar Upazila, Jashore district of Bangladesh. A standardized questionnaire was used to collect information regarding the socio-economic status, time spent watching television, video games playing, computer, and smart mobile phone use through face-to-face interviews. Age- and sex-specific body mass index (BMI) cut-off values for overweight and obesity were determined for Asian adolescents by the International Obesity Task Force (IOTF). Multinomial logistic regression analysis was carried out to determine the association between electronic media use with overweight and obesity. Findings The findings suggest that the overall prevalence of overweight and obesity was 13.5% and 25.2%, respectively. Among the total adolescent students, about 49.1% highly (above 3 hours per day) spent their time on EM use whereas 30.6% moderately (≥121 to 180 min/day) use EM. The regression analysis showed that spending high time using total screen-based electronic devices, television viewing, video game playing, computer use, and smartphone use were significantly associated with overweight (RRR: 7.36, 95% CI: 3.64-11.54; RRR: 4.58, 95% CI: 1.46-7.95; RRR: 4.45, 95% CI: 2.75-6.12; RRR: 3.18, 95% CI: 1.87-4.70; RRR: 2.15, 95% CI: 1.23-3.51) and obesity (RRR: 8.72, 95% CI: 4.64-12.54; RRR: 2.89, 95% CI: 1.31-5.21; RRR: 3.88, 95% CI: 1.74-5.13; RRR: 3.08, 95% CI: 1.32-4.86; RRR: 1.19, 95% CI: 0.93-1.48) in adolescents, respectively. Conclusion The results support the total time spent using electronic media was associated with an increased risk of being overweight and obesity. Finally, this study strongly suggests the proper use of electronic media may be necessary to reduce the risk of being overweight and obesity in early adolescents.